Hubungan Pengetahuan Ibu, Lingkungan dan Status Gizi dengan Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Rawat Inap Sidomulyo Pekanbaru ahun 2021 - Bayu Afdhal Masril; Nila Puspita Sari; Jihan Natassa (Jurnal Kesehatan Komunitas, 2022)
Acute respiratory infections are infections that are possible to relate with upper respiratory dan lower respiratory infections that can cause various diseases from mild to severe infections. This study aimed to know the association between a mother’s knowledge, ventilation, occupancy density, smoke, and nutritional status with an acute respiratory infection. This study was quantitative research with a cross-sectional study. Data collected in Sidomulyo Inpatient’s Public Health Centre working area from Juli-September 2021. Populations were a mother who has a toddler. Samples were collected as proportional simple random sampling for 163 respondents using a questionnaire. Statistic analysis used the chi-square test to know the association between knowledge, ventilation, occupancy density, smoke, and nutritional status with an acute respiratory infection. The results showed that mother’s knowledge, ventilation, occupancy density, smoke, and nutritional status (p-value = 0,022; 0,024; 0,029; 0,027; and 0,029) with acute respiratory infection in Sidomulyo Inpatient’s Public Health Centre. The Suggestion is to educate people for improving the health of the community.